A Shiny Fragmentary Skeleton: The World Bank and Workers' Human Rights in the 2013 World Development Report - Etchichury, Horacio Javier (2014)
This article intends to describe the scope of the right to work in the World Bank's 2013 World Development Report: Jobs. In the first place, the article analyses, from a legal prospective, the right to work as phrased in the main international human rights instruments. Academic comments and judicial developments are included in the analysis, as well as international organisms' contributions. Second, the article compares this interpretation to the World Bank's ideas on the issue, as expressed in the report. Through this comparison, the Bank's contradictions and restrictive constructions become apparent. Finally, the article describes the risks faced by borrower countries if their policies are designed according to the World Bank proposals.